2013
DOI: 10.1128/jvi.00385-13
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus Large T Antigen Has Growth-Promoting and Inhibitory Activities

Abstract: cMerkel cell carcinoma (MCC) is a rare and aggressive form of skin cancer. In at least 80% of all MCC, Merkel cell polyomavirus (MCPyV) DNA has undergone clonal integration into the host cell genome, and most tumors express the MCPyV large and small T antigens. In all cases of MCC reported to date, the integrated MCPyV genome has undergone mutations in the large T antigen. These mutations result in expression of a truncated large T antigen that retains the Rb binding or LXCXE motif but deletes the DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
157
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 44 publications
13
157
0
Order By: Relevance
“…13,14 Emerging data implicate maintenance and expression of the polyomavirus large T antigen in cell cycle dysregulation and the pathogenesis of viral transformation leading to Merkel cell carcinoma. 12,[15][16][17][18][19][20][21] Although the molecular role of Merkel cell polyomavirus is quickly evolving, the overall biology of Merkel cell carcinoma is poorly understood. Moreover, the presence of polyomavirus alone is not sufficient for carcinogenesis, namely in those Merkel cell carcinoma cases considered as polyomavirusnegative.…”
mentioning
confidence: 99%
“…13,14 Emerging data implicate maintenance and expression of the polyomavirus large T antigen in cell cycle dysregulation and the pathogenesis of viral transformation leading to Merkel cell carcinoma. 12,[15][16][17][18][19][20][21] Although the molecular role of Merkel cell polyomavirus is quickly evolving, the overall biology of Merkel cell carcinoma is poorly understood. Moreover, the presence of polyomavirus alone is not sufficient for carcinogenesis, namely in those Merkel cell carcinoma cases considered as polyomavirusnegative.…”
mentioning
confidence: 99%
“…The identification of a tumor with intact full-length LT but a mutated viral origin sequence supports this hypothesis (26). Later studies have since suggested that the C-terminal helicase domain may contain other functions that oppose tumorigenesis (16,24). Our previous work indicated that expression of full-length MCV LT activates a dramatic DNA damage response (DDR) that is antagonistic to tumorigenesis; this activity activates p53 and induces a growthinhibiting phenotype (16).…”
Section: Merkel Cell Polyomavirus (Mcv)mentioning
confidence: 68%
“…Our previous study demonstrated that the C-terminal portion of LT activates p53 and promotes growth inhibition (16). Cheng et al (24) also reported that the C-terminal 100 amino acids of MCV LT have a cell growth-inhibiting effect. The underlying mechanism of these findings was not completely established.…”
Section: Prevention Of MCV Lt Ser-816 Phosphorylation Partially Rescumentioning
confidence: 99%
See 2 more Smart Citations